Prevalence of Dysmenorrhea and Associated Factors among Secondary School Female Students in Rapti Rural Municipality, Dang, Nepal - Sharma, Aliya; Marasini, Baburam (Journal of Multidisciplinary Research Advancements, 2025)
Dysmenorrhea is one of the most common menstrual problems among adolescent females. It is defined as painful cramps or pain of uterine origin that happens during or before menstruation. It has a severe impact on day-to-day activities, including school absenteeism and reduced social and physical activity. Hence, this study aimed to assess the prevalence of dysmenorrhea and its associated factors among secondary school female students in Rapti Rural Municipality, Dang, Nepal. A cross-sectional study was conducted from April 2024 to September 2024 among female secondary school students in government schools in Rapti Rural Municipality, Dang, Nepal. Students were selected through a proportionate stratified random sampling technique. A self-administered questionnaire was used to collect data from 316 adolescent girls; however, only 312 were included in the study. Data were checked, coded, and entered into EpiData (version 3.1), and analysed in SPSS version 26 using both descriptive and inferential statistics. The prevalence of dysmenorrhea was found to be 86.2%; among them, half of the respondents experienced severe pain (43.5%), followed by mild (41.6%) and moderate (14.9%). Ethnicity (χ2=12.69, p=0.026), family history of dysmenorrhea (χ2=20.358, p=0.001), menstrual cycle length (χ2=6.729, p=0.035) and experience of spotting in between periods (χ2=8.406, p=0.015) had statistically significant associations with dysmenorrhea. Severity of dysmenorrhea was found to be significantly associated with school absenteeism (χ2=33.428, p=0.001), source of information regarding menstruation (χ2=21.463, p=0.006), coping strategies like taking bed rest (χ2=18.736, p=0.001), self-medication (χ2=10.067, p=0.007), applying massage (χ2=8.86, p=0.012) and being hospitalised due to pain (χ2=7.135, p=0.028). Dysmenorrhea is a serious public health concern among adolescent girls in Rapti Rural Municipality. Factors such as family history, ethnicity, and irregular menstrual cycles significantly contribute to this burden that leads to notable school absenteeism and reliance on inadequate coping methods like self-medication. Dysmenorrhea places a substantial social and educational burden on affected students and their families, highlighting the need for better awareness and improved practical support in schools.